PENGARUH KUALITAS LAYANAN ATAS KEPUASAN SISWA DAN DAMPAKNYA TERHADAP LOYALITAS SISWA DI SMK KRISTEN SALATIGA - Noventris Ratnawati Radja; Supramono Supramono; Bambang Suteng Sulasmono (Satya Widya, 2013)
School as a public Education institute must serve good quality education especially for the students, so that the students will feel satisfied to the service and show their loyal attitude toward the school. This study was done at SMK Kristen Salatiga to identify the effect of the service quality with student’s satisfaction and its effect to the student’s loyalty toward the school. The sample of this study was 100 students of SMK Kristen Salatiga grade II and III out of 261 populations. The result of the study showed that; (1) The quality service at SMK Kristen Salatiga have a positive impact and significant to the SMK Kristen Salatiga student’s satisfaction. (2) The student’s satisfaction have a positive influence and significant to their loyalty. (3) There is no correlation between the service quality and the student’s loyalty at SMK Kristen Salatiga toward the student’s satisfaction variable. (4) The quality service at SMK Kristen Salatiga directly effect and not significant to the student’s loyalty.